Distribution of bacteria in tropical freshwater fish and ponds - Kasing, Apun; Asiah M., Yusof; Kumbang J, Jugang (Taylor & Francis Ltd., 1999)
Bacteriological examination of the various organs (liver, kidney, intestine and inner muscle) of four freshwater fish species belonging to the family cyprininae reared in experimental ponds were compared to those reared in conventional pond. A total of 16 bacterial species were recovered from the water samples and the various organs of the fish. The intestines of all the fish species harboured the most number of different bacterial species. No bacteria was found in the muscle of any of the fish. In general, the bacterial species isolated from the intestine were also found in the water samples from the ponds. The common species found in the intestine of the fish belonged to seven Gram negative bacterial species: Aeromonas hydrophila, Citrobacter freundii, Escherichia coli, Enterobacter aerogenes, Klebsiella sp., Pseudomonas sp, Vibrio anguillarum and three Gram positive bacterial species: Bacillus sp., Listeria and Staphylococcus. The presence of the former group of bacteria which are members of the family Enterobacteriaceae and Vibrio-Aeromonas is a cause for concern as these organisms are potential enteropathogens, and any mishandling of the fish can lead to the transmission of the pathogen to humans. The type of bacterial species present in the water of the conventional ponds were similar to those found in the experimental ponds.